ANALISIS PENERAPAN BRILINK DI BANK BRI KOTA MADIUN SEBAGAI UPAYA MENDORONG FINANCIAL INCLUSION - Herman Ahmadi (Universitas PGRI Madiun, 2018)
The role of the financial system becomes relatively important in a country's economy in today's globalization era. The financial sector as part of the economic backer of the state has an important task in supporting the economic activities of the poor so that they can still do its activities. According to Bank Indonesia the form of an inclusive financial national strategy is the right of everyone to have access and full service from financial institutions in a timely, , informative, and affordable costs, with full respect for the dignity and prestige of PT. BRI (Persero), Tbk. Madiun Branch Office is one of the branch offices of PT. Bank Rakyat Indonesia (Persero), Tbk. His job is to carry out all orders that have been established by the head office and provide banking products services, including being a manager of BRILink for Madiun and surrounding areas. Research Objectives Describe the sustainability of BRILink services, as well as describe the barriers that exist in the implementation of BRILink PT. BRI (Persero), and the successful implementation of BRILink PT. BRI (Persero), Tbk. Branch Office Madiun can encourage financial inclusion in Madiun and surrounding areas. A well-developed financial sector will encourage economic activity, PT. BRI (Persero), Tbk. Branch Office Madiun can only be enjoyed by the city community freely. The low level of public financial literacy and the geographic condition of the Madiun region that is not accessible by access to banking services are the factors that hinder financial inclusion. and must fix itself from the many obstacles in the implementation of BRIlink so that more users and agents can improve the quality of life due to the ease of service BRIlink, PT. BRI (Persero), Tbk. Madiun Branch Offices often evaluate the implementation of BRIlink, as well as minimize constraints, and increase training in the use of EDC machines